An AB2-type Laves phase hydrogen storage high-entropy alloy, its preparation method and application
Patent Information
- Application Number
- CN202311838503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-28
AI Technical Summary
[0006]鉴于以上分析,本发明旨在提供一种AB2型Laves相储氢高熵合金及其制备方法和应用,用以解决现有技术中储氢合金吸氢、放氢温度偏高,循环性能不明,高熵合金的成分不易控制、合金由多相组成等问题中的至少一个
[0023] 1. This invention provides an AB2 type Laves phase hydrogen storage high-entropy alloy with the chemical formula TiZrCrMnFeCo. 1-x Ni x The hydrogen storage high-entropy alloy contains no rare earth or sparingly soluble elements, has a high-abundance Laves single-phase structure, and can rapidly absorb and release hydrogen at room temperature.
Smart Images

Figure CN117821826B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen storage materials technology, and specifically relates to an AB2 type Laves phase hydrogen storage high-entropy alloy, its preparation method and application. Background Technology
[0002] With the depletion of fossil fuels and severe environmental pollution, the search for renewable and clean energy sources to replace fossil fuels has become a focus of human attention. Hydrogen energy is considered the most promising alternative to fossil fuels. It is lightweight, has a large storage capacity, high energy density, and produces clean, pollution-free combustion products. The key to hydrogen energy utilization is the development of high-density hydrogen storage technology. Currently, the main hydrogen storage methods include physical storage using gaseous and liquid carriers, and solid-state storage. Solid-state hydrogen storage, with its advantages of high safety, convenient transportation, and high storage density, is considered the most promising method.
[0003] Solid-state hydrogen storage primarily utilizes metal hydride hydrogen storage materials. Rare-earth hydrogen storage materials, represented by LaNi5, have been widely used in Ni-H fuel cells, but their hydrogen storage capacity is relatively low, and the cost of rare-earth materials is also high. V-based solid solution hydrogen storage alloys experience high cycle capacity decay, and their low plateau pressure makes hydrogen dehydrogenation difficult. Mg-based alloys also face dehydrogenation challenges due to their excessively high hydride thermal stability, with dehydrogenation temperatures generally exceeding 300 degrees Celsius. AB-type TiFe hydrogen storage alloys offer advantages such as low cost and good thermodynamics and kinetics, but they are difficult to activate and have poor resistance to poisoning.
[0004] Nygard et al. discovered that TiVCrNb alloys do not require activation [MM] G.Ek, D.Karlsson, MH [M. Sahlberg, and B. Chauback, Acta Materialia 175, 121 (2019).] High-entropy hydrogen storage alloys can absorb 1.96 wt.% H2 at room temperature and appropriate pressure, but dehydrogenation is difficult. Currently developed high-entropy hydrogen storage alloys still suffer from problems such as high dehydrogenation temperature and unclear cycle performance.
[0005] In conclusion, developing a novel high-entropy hydrogen storage alloy with excellent comprehensive performance and its preparation method has significant practical application value. Summary of the Invention
[0006] Based on the above analysis, the present invention aims to provide an AB2 type Laves phase hydrogen storage high-entropy alloy, its preparation method and application, to solve at least one of the following problems in the prior art: high hydrogen absorption and desorption temperatures of hydrogen storage alloys, unclear cycle performance, difficulty in controlling the composition of high-entropy alloys, and alloys composed of multiple phases.
[0007] Based on the above analysis, this invention discloses an AB2-type Laves phase hydrogen storage high-entropy alloy, the chemical formula of which is: TiZrCrMnFeCo 1-x Ni x In the chemical formula, x represents the atomic ratio, where 0 ≤ x < 1.
[0008] Furthermore, in the chemical formula, 0.5 ≤ x < 0.95.
[0009] Furthermore, the hydrogen storage high-entropy alloy has a high-abundance C14 Laves phase structure.
[0010] Furthermore, the hydrogen storage high-entropy alloy is prepared by melting, encapsulation, and quenching.
[0011] The present invention also discloses a method for preparing an AB2 type Laves phase hydrogen storage high-entropy alloy, wherein the preparation method involves arc vacuum melting of metal raw materials under an inert atmosphere, followed by heat treatment and rapid cooling after encapsulation.
[0012] Furthermore, the preparation method includes:
[0013] S1, according to the chemical formula TiZrCrMnFeCo 1-x Ni x The raw materials are prepared with a purity of ≥99.9%. Under an inert atmosphere, the metal raw materials are placed in the crucible of an electric arc furnace and melted in an electric arc vacuum. After the alloy is completely melted and cooled, an alloy ingot is formed. The alloy ingot is turned over and melted repeatedly 3-5 times to obtain an ingot sample of the hydrogen storage high entropy alloy.
[0014] S2, after wrapping the ingot sample with tantalum foil, seal it in a high-temperature resistant quartz tube filled with inert gas;
[0015] S3, the ingot sample encapsulated in the quartz tube is subjected to quenching treatment, which includes heat treatment and rapid cooling.
[0016] S4. The quenched alloy sample is mechanically crushed to obtain the finished AB2 type Laves phase hydrogen storage high-entropy alloy.
[0017] Furthermore, in step S1, the metal raw materials are placed in the electric arc furnace crucible from bottom to top in order of increasing melting point.
[0018] Furthermore, in S1, the vacuum degree of the electric arc vacuum melting is (0.3-0.5)×10⁻⁶. -2 Pa.
[0019] Furthermore, in S3, the heat treatment heating rate is 5-10℃ / min, the holding temperature is 900-1200℃, and the holding time is 12-24h.
[0020] This invention also discloses the application of an AB2-type Laves phase hydrogen storage high-entropy alloy in hydrogen storage. The AB2-type Laves phase hydrogen storage high-entropy alloy absorbs hydrogen under conditions of 350-400℃ and 3-5MPa, and is cycled 2-3 times to obtain the activity of the hydrogen storage high-entropy alloy, which is then used for hydrogen storage.
[0021] The objective of this invention is mainly achieved through the following technical solutions:
[0022] Compared with the prior art, the present invention can achieve at least one of the following technical effects:
[0023] 1. This invention provides an AB2 type Laves phase hydrogen storage high-entropy alloy with the chemical formula TiZrCrMnFeCo. 1-x Ni x The hydrogen storage high-entropy alloy contains no rare earth or sparingly soluble elements, has a high-abundance Laves single-phase structure, and can rapidly absorb and release hydrogen at room temperature.
[0024] 2. The hydrogen storage high-entropy alloy of the present invention has the characteristics of low cost. The system of the present invention does not contain rare earth and precious metal elements, and the raw material cost is low. The preparation method is simple and the parameters are easy to control, making it suitable for industrial mass production. In 50 cycle performance tests, the capacity decay does not exceed 15%, and the cycle performance is good.
[0025] 3. The preparation method of the hydrogen storage high-entropy alloy provided by the present invention is simple. The composition contains only one volatile element, Mn. By adding appropriate burn-off, the alloy composition can be accurately controlled, and the composition is easy to control. It has low risk and is suitable for industrial production. It can accurately control the composition and phase purity of the high-entropy alloy and precisely regulate the hydrogen storage performance of the hydrogen storage high-entropy alloy.
[0026] Other features and advantages of the invention will be set forth in the following description, and in part will be obvious from the description or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures particularly pointed out in the written description and the accompanying drawings. Attached Figure Description
[0027] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0028] Figure 1(a) is the simulated variable-temperature uniaxial phase diagram of the TiZrCrMnFeCo alloy of the present invention, and Figure 1(b) is the simulated variable-temperature uniaxial phase diagram of the TiZrCrMnFeCo alloy of the present invention. 0.6 Ni 0.4 The simulated temperature-variable uniaxial phase diagram of the alloy is shown in Figure 1(c), which is the TiZrCrMnFeCo alloy of this invention. 0.2 Ni0.8 The simulated temperature-variable uniaxial phase diagram of the alloy is shown in Figure 1(d), which is the TiZrCrMnFeCo alloy of this invention. 0.05 Ni 0.95 Simulation of variable-temperature uniaxial phase diagrams for alloys;
[0029] Figure 2 The XRD spectra of the hydrogen storage high-entropy alloys of Examples 1 and 2 of this invention are shown below.
[0030] Figure 3 This is a graph showing the hydrogen absorption and desorption kinetics of the hydrogen storage high-entropy alloy of Example 1 of the present invention at room temperature.
[0031] Figure 4 This is a graph showing the hydrogen absorption and desorption kinetics of the hydrogen storage high-entropy alloy of Example 2 of the present invention at room temperature;
[0032] Figure 5 This is a graph showing the hydrogen absorption and desorption kinetics of the hydrogen storage high-entropy alloy of Example 3 of the present invention at room temperature.
[0033] Figure 6 This is a graph showing the hydrogen absorption and desorption kinetics of the hydrogen storage high-entropy alloy of Example 4 of the present invention at room temperature.
[0034] Figure 7 This is the PCT curve of the hydrogen storage high-entropy alloy of Example 1 of the present invention at room temperature;
[0035] Figure 8 This is the PCT curve of the hydrogen storage high-entropy alloy of Example 2 of the present invention at room temperature;
[0036] Figure 9 This is the PCT curve of the hydrogen storage high-entropy alloy of Example 3 of the present invention at room temperature;
[0037] Figure 10 This is the PCT curve of the hydrogen storage high-entropy alloy of Example 4 of the present invention at room temperature. Detailed Implementation
[0038] The following detailed description, in conjunction with specific embodiments, provides an AB2-type Laves phase hydrogen storage high-entropy alloy, its preparation method, and its applications. These embodiments are for comparative and illustrative purposes only, and the present invention is not limited to these embodiments.
[0039] On one hand, embodiments of the present invention provide an AB2-type Laves phase hydrogen storage high-entropy alloy, the chemical formula of which is: TiZrCrMnFeCo 1-x Ni x In the chemical formula, x represents the atomic ratio, where 0 ≤ x < 1.
[0040] Compared with the prior art, the chemical formula of this invention is TiZrCrMnFeCo. 1-x Ni x The hydrogen storage high-entropy alloy contains no rare earth elements or sparingly soluble elements and can rapidly absorb and release hydrogen at room temperature.
[0041] AB2-type alloys with a C14 Laves phase structure typically possess hydrogen storage capacity, with a theoretical capacity hydride molecular formula of AB2H6. In the composition of this invention, TiZr is an A-side hydrogen-absorbing element, and CrMnFeCo... 1-x Ni x As the non-hydrogen-absorbing element on the B side, thermodynamic phase diagram calculations show that the high-entropy alloy combining the two has a high abundance of C14 Laves phase. Alloys in the range of 0≤x<1 can maintain the C14 Laves single-phase structure. The experimentally prepared samples prove that they have a C14 Laves single-phase structure and have the ability to store hydrogen through rapid cycling at room temperature.
[0042] Specifically, in the chemical formula, 0.5 ≤ x ≤ 0.95.
[0043] C14 Laves is a hexagonal phase commonly found in AB2-type transition metal compounds. This crystal structure contains large tetrahedral and octahedral spaces, facilitating the entry and exit of hydrogen atoms, thus possessing a certain hydrogen storage capacity. In the system of this invention, Ti and Zr have a high affinity for hydrogen atoms and are considered A-side hydrogen-absorbing elements, while Cr, Mn, Fe, Co, and Ni are B-side non-hydrogen-absorbing elements. Alloys within this composition range exhibit a high abundance of the C14 Laves phase and all possess a certain hydrogen storage capacity; excessively high or low atomic ratios cause the alloy to lose the high abundance of the C14 Laves phase, thereby losing its hydrogen storage capacity.
[0044] Specifically, the hydrogen storage high-entropy alloy has a high-abundance C14 Laves phase structure.
[0045] The hydrogen storage high-entropy alloy has a space group of P63 / mmc; lattice constants: a is about 0.49 nm, c is about 0.81 nm, grain size: about 100-300 μm. The C14 Laves phase structure has a large number of tetrahedral and octahedral spaces, which facilitates the diffusion of hydrogen atoms inside the alloy, thus giving the alloy a certain hydrogen storage capacity.
[0046] Specifically, the hydrogen storage high-entropy alloy is prepared by melting, encapsulation and quenching.
[0047] On the other hand, embodiments of the present invention provide a method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy, wherein the preparation method involves arc vacuum melting of metal raw materials under an inert atmosphere, followed by heat treatment and rapid cooling after encapsulation.
[0048] Specifically, the preparation method includes:
[0049] S1, according to the chemical formula TiZrCrMnFeCo 1-x Ni x The raw materials are prepared with a purity of ≥99.9%. Under an inert atmosphere, the metal raw materials are placed in the crucible of an electric arc furnace and melted in an electric arc vacuum. After the alloy is completely melted and cooled, an alloy ingot is formed. The alloy ingot is turned over and melted repeatedly 3-5 times to obtain an ingot sample of the hydrogen storage high entropy alloy.
[0050] S2, after wrapping the ingot sample with tantalum foil, seal it in a high-temperature resistant quartz tube filled with inert gas;
[0051] S3, the ingot sample encapsulated in the quartz tube is subjected to quenching treatment, which includes heat treatment and rapid cooling.
[0052] S4. The quenched alloy sample is mechanically crushed to obtain the finished AB2 type Laves phase hydrogen storage high-entropy alloy.
[0053] The method for preparing the hydrogen storage high-entropy alloy provided by this invention is simple, the composition is easy to control, and the risk is low, making it suitable for industrial production.
[0054] Phase purity is mainly determined by composition, and is also affected by heat treatment process. Heat treatment temperature and holding time have a great influence on the content of Laves phase in the same alloy. The preparation method of this invention can accurately control the composition and phase purity of high-entropy alloys, and precisely regulate the hydrogen storage performance of hydrogen storage high-entropy alloys. Hydrogen storage performance is controlled by alloy composition, phase composition and particle size. Different alloy compositions and phase compositions result in different hydrogen storage capacities. Particle size affects hydrogen storage kinetics. Generally, smaller particles have faster hydrogen absorption / desorption rates.
[0055] High-entropy alloys exhibit high atomic disorder and large lattice distortion, facilitating the internal diffusion of hydrogen atoms and ensuring structural stability during hydrogen absorption / dehydrogenation. The high-entropy effect enables the alloy to form a solid solution single-phase structure. This invention pertains to a multi-component high-entropy alloy system, where component atoms are randomly distributed across lattice sites in a C14 Laves structure, exhibiting a long-range disordered structure that results in large lattice distortion. This facilitates the internal diffusion of hydrogen atoms, giving the alloy a certain hydrogen storage capacity. Furthermore, hydrogen atoms are less likely to disrupt the disordered lattice structure during diffusion, preventing pulverization and ensuring the alloy's cyclic hydrogen storage performance. The high-entropy effect is one of the four fundamental effects of high-entropy alloys; the large entropy value makes high-entropy alloys readily form a Laves single-phase structure.
[0056] Preferably, Mn is volatile, and an addition of approximately 4 wt.% is used for loss on ignition.
[0057] Specifically, in step S1, the metal raw materials are placed in the electric arc furnace crucible from bottom to top in order of increasing melting point.
[0058] Since low-melting-point alloys are volatile, placing them at the bottom can suppress volatilization to the greatest extent, thereby ensuring the accuracy of the alloy composition during smelting.
[0059] Preferably, the metal raw materials are titanium particles, zirconium blocks, chromium sheets, manganese blocks, iron blocks, cobalt sheets, and nickel sheets.
[0060] Preferably, the inert atmosphere is an argon atmosphere.
[0061] Specifically, in S1, the vacuum degree of the electric arc vacuum melting is (0.3-0.5)×10⁻⁶. -2 Pa.
[0062] Preferably, in step S2, the vacuum level inside the quartz tube is -0.07 to -0.09 MPa.
[0063] The main purpose of controlling the vacuum level is to prevent oxidation, which will deteriorate or even cause the alloy to lose its hydrogen storage performance.
[0064] Specifically, in step S3, the high-temperature resistant quartz tube containing the TiZrCrMnFeCo ingot sample is placed in the constant temperature zone of a vacuum tube furnace, and the heat treatment program is set as follows: the furnace temperature is raised from room temperature to 900-1200℃ in 220 minutes, and then held at 1130℃ for 12-24 hours. After the holding program is completed, the sample is taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0065] The heat treatment process is to fully dissolve the alloy atoms and increase the content of C14 Laves phase in the alloy, while quenching is to retain the C14 Laves structural phase at high temperatures.
[0066] Specifically, in step S2, the ingot sample is wrapped with tantalum foil and placed in a high-temperature resistant quartz tube. A vacuum mechanical pump is used to reduce the vacuum level inside the quartz tube to -0.07 to -0.09 MPa. Then, the open end of the quartz tube is burned under an oxyhydrogen flame to close it, thereby achieving the purpose of sealing the quartz tube.
[0067] The sample was sealed in a quartz tube to prevent oxidation during the heat treatment process.
[0068] Specifically, in S3, the heat treatment heating rate is 5-10℃ / min, the holding temperature is 900-1200℃, and the holding time is 12-24h.
[0069] Preferably, rapid cooling involves placing the heat-treated ingot alloy in liquid nitrogen or water.
[0070] Specifically, in step S3, the high-temperature resistant quartz tube containing the ingot sample is placed in the constant temperature zone of a vacuum tube furnace. After the heat treatment holding process is completed, the sample is taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0071] Specifically, in step S3, the quartz tube is broken, the quenched sample is taken out and transferred to a glove box, and the quenched sample is mechanically crushed using a stainless steel mortar. The crushed powder is then sieved to obtain a high-entropy alloy powder sample that can be used for hydrogen storage performance testing.
[0072] Testing the hydrogen storage performance of an alloy requires breaking it into powder to increase the contact area between hydrogen molecules and the alloy surface.
[0073] Preferably, in step S4, the quenched alloy sample is mechanically crushed using a stainless steel mortar.
[0074] Preferably, the particle size of the crushed alloy powder is 200-300 mesh.
[0075] Uniform particles with this size facilitate the adsorption and decomposition of hydrogen molecules. Particles that are too large will make it more difficult for hydrogen atoms to enter the alloy particles, while particles that are too small will be easily oxidized during experimental operations.
[0076] On the other hand, embodiments of the present invention provide an application of the AB2-type Laves phase hydrogen storage high-entropy alloy in hydrogen storage. The AB2-type Laves phase hydrogen storage high-entropy alloy absorbs hydrogen under conditions of 350-400℃ and 3-5MPa, and is cycled 2-3 times to obtain the activity of the hydrogen storage high-entropy alloy, which is then used for hydrogen storage.
[0077] The hydrogen absorption conditions set by this invention can fully activate the sample and open the channels for hydrogen atoms to enter and exit, thereby facilitating subsequent hydrogen storage performance testing.
[0078] The alloy contains only one volatile element, Mn, and the alloy composition can be accurately controlled by adding appropriate burn-off. C14Laves has a wide temperature threshold, making it easy to prepare a single-phase structure. The hydrogen storage capacity of the alloy is related to the Ni / Co content, and the capacity gradually increases with the increase of x. The hydrogen storage performance of the alloy can be easily changed by adjusting the alloy composition.
[0079] The advantages of precise control of composition and process parameters of the AB2 type Laves phase hydrogen storage high-entropy alloy of the present invention will be demonstrated below with specific embodiments and comparative examples.
[0080] Example 1: TiZrCrMnFeCo
[0081] The preparation method is as follows:
[0082] Titanium particles, zirconium blocks, chromium sheets, manganese blocks, iron blocks, and cobalt sheets with a purity ≥99.9% were selected. These metal raw materials were weighed according to the elemental mass ratio of the chemical formula TiZrCrMnFeCo: 13.27 g of titanium, 25.28 g of zirconium, 14.41 g of chromium, 15.23 g of manganese, 15.48 g of iron, and 16.33 g of cobalt. The weighed metal raw materials were placed in a crucible of a vacuum arc furnace in order of increasing melting point. The furnace was evacuated to a vacuum degree below 0.003 Pa, and then argon gas at 0.06 MPa was introduced as a protective gas for arc vacuum melting. After the alloy was completely melted and cooled, an alloy ingot was formed. The alloy ingot was turned over and melted repeatedly four times to obtain the TiZrCrMnFeCo alloy ingot.
[0083] The TiZrCrMnFeCo ingot sample was wrapped in tantalum foil and placed in a quartz tube that can withstand a high temperature of 1200℃. The vacuum degree inside the quartz tube was reduced to below -0.09MPa using a vacuum mechanical pump. Then, the open end of the quartz tube was closed by burning it under an oxyhydrogen flame, thus achieving the purpose of sealing the quartz tube.
[0084] The high-temperature resistant quartz tube containing the TiZrCrMnFeCo ingot sample was placed in the isothermal zone of a vacuum tube furnace, and the heat treatment program was set as follows: the furnace temperature was raised from room temperature to 1130℃ in 220 minutes, and then held at 1130℃ for 16 hours. After the holding program was completed, the sample was taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0085] The quartz tube was broken, and the quenched TiZrCrMnFeCo sample was taken out and transferred to a glove box. The quenched sample was mechanically crushed using a stainless steel mortar. The crushed powder was passed through a 300-mesh sieve to obtain a TiZrCrMnFeCo high-entropy alloy powder sample that can be used for hydrogen storage performance testing.
[0086] Example 2: TiZrCrMnFeCo 0.05 Ni 0.95
[0087] The preparation method is as follows:
[0088] Titanium particles, zirconium blocks, chromium sheets, manganese blocks, iron blocks, cobalt sheets, and nickel sheets with a purity ≥ 99.9% were selected. These metals are classified according to the chemical formula TiZrCrMnFeCo. 0.05 Ni 0.95The following elemental mass ratios were measured: 13.28 g of titanium, 25.30 g of zirconium, 14.42 g of chromium, 15.24 g of manganese, 15.49 g of iron, 0.82 g of cobalt, and 15.46 g of nickel. The weighed metal raw materials were placed in a crucible of a vacuum arc furnace in order of increasing melting point. A vacuum was drawn to below 0.003 Pa, and then argon gas at 0.06 MPa was introduced as a protective gas. Arc vacuum melting was performed. After the alloy was completely melted and cooled, an alloy ingot was formed. The ingot was flipped and melted repeatedly four times to obtain TiZrCrMnFeCo. 0.05 Ni 0.95 Alloy ingots.
[0089] TiZrCrMnFeCo 0.05 Ni 0.95 The ingot sample was wrapped in tantalum foil and placed in a quartz tube that could withstand a high temperature of 1200℃. The vacuum level inside the quartz tube was reduced to below -0.09MPa using a vacuum mechanical pump. Then, the open end of the quartz tube was closed by burning it under an oxyhydrogen flame, thus achieving the purpose of sealing the quartz tube.
[0090] Encapsulated with TiZrCrMnFeCo 0.05 Ni 0.95 The ingot sample was placed in the constant temperature zone of a vacuum tube furnace in a high-temperature resistant quartz tube. The heat treatment program was set as follows: the furnace temperature was raised from room temperature to 950℃ in 180 minutes, and then held at 950℃ for 18 hours. After the holding program was completed, the sample was taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0091] Break the quartz tube and remove the quenched TiZrCrMnFeCo. 0.05 Ni 0.95 The sample was transferred to a glove box, and the quenched sample was mechanically crushed using a stainless steel mortar. The crushed powder was then passed through a 300-mesh sieve to obtain TiZrCrMnFeCo, which can be used for hydrogen storage performance testing. 0.05 Ni 0.95 High-entropy alloy powder sample.
[0092] Example 3: TiZrCrMnFeCo 0.6 Ni 0.4
[0093] The preparation method is as follows:
[0094] Titanium particles, zirconium blocks, chromium sheets, manganese blocks, iron blocks, cobalt sheets, and nickel sheets with a purity ≥ 99.9% were selected. These metals are classified according to the chemical formula TiZrCrMnFeCo. 0.6 Ni 0.4The following elemental mass ratios were measured: 13.27 g of titanium, 25.29 g of zirconium, 14.42 g of chromium, 15.23 g of manganese, 15.48 g of iron, 9.80 g of cobalt, and 6.51 g of nickel. The weighed metal raw materials were placed in a crucible of a vacuum arc furnace in order of increasing melting point. A vacuum was drawn to below 0.003 Pa, and then argon gas at 0.06 MPa was introduced as a protective gas. Arc vacuum melting was performed. After the alloy was completely melted and cooled, an alloy ingot was formed. The ingot was flipped and melted repeatedly four times to obtain TiZrCrMnFeCo. 0.6 Ni 0.4 Alloy ingots.
[0095] TiZrCrMnFeCo 0.6 Ni 0.4 The ingot sample was wrapped in tantalum foil and placed in a quartz tube that could withstand a high temperature of 1200℃. The vacuum level inside the quartz tube was reduced to below -0.09MPa using a vacuum mechanical pump. Then, the open end of the quartz tube was closed by burning it under an oxyhydrogen flame, thus achieving the purpose of sealing the quartz tube.
[0096] Encapsulated with TiZrCrMnFeCo 0.6 Ni 0.4 The ingot sample was placed in the constant temperature zone of a vacuum tube furnace in a high-temperature resistant quartz tube. The heat treatment program was set as follows: the furnace temperature was raised from room temperature to 1100℃ in 180 minutes, and then held at 1100℃ for 18 hours. After the holding program was completed, the sample was taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0097] Break the quartz tube and remove the quenched TiZrCrMnFeCo. 0.6 Ni 0.4 The sample was transferred to a glove box, and the quenched sample was mechanically crushed using a stainless steel mortar. The crushed powder was then passed through a 300-mesh sieve to obtain TiZrCrMnFeCo, which can be used for hydrogen storage performance testing. 0.6 Ni 0.4 High-entropy alloy powder sample.
[0098] Example 4: TiZrCrMnFeCo 0.2 Ni 0.8
[0099] The preparation method is as follows:
[0100] Titanium particles, zirconium blocks, chromium sheets, manganese blocks, iron blocks, cobalt sheets, and nickel sheets with a purity ≥ 99.9% were selected. These metals are classified according to the chemical formula TiZrCrMnFeCo. 0.2 Ni 0.8The following elemental mass ratios were measured: 13.27 g of titanium, 25.30 g of zirconium, 14.42 g of chromium, 15.23 g of manganese, 15.49 g of iron, 3.27 g of cobalt, and 13.02 g of nickel. The weighed metal raw materials were placed in a crucible of a vacuum arc furnace in order of increasing melting point. A vacuum was drawn to below 0.003 Pa, and then argon gas at 0.06 MPa was introduced as a protective gas. Arc vacuum melting was performed. After the alloy was completely melted and cooled, an alloy ingot was formed. The ingot was flipped and melted repeatedly four times to obtain TiZrCrMnFeCo. 0.2 Ni 0.8 Alloy ingots.
[0101] TiZrCrMnFeCo 0.2 Ni 0.8 The ingot sample was wrapped in tantalum foil and placed in a quartz tube that could withstand a high temperature of 1200℃. The vacuum level inside the quartz tube was reduced to below -0.09MPa using a vacuum mechanical pump. Then, the open end of the quartz tube was closed by burning it under an oxyhydrogen flame, thus achieving the purpose of sealing the quartz tube.
[0102] Encapsulated with TiZrCrMnFeCo 0.2 Ni 0.8 The ingot sample was placed in the constant temperature zone of a vacuum tube furnace in a high-temperature resistant quartz tube. The heat treatment program was set as follows: the furnace temperature was raised from room temperature to 1030℃ in 180 minutes, and then held at 1030℃ for 18 hours. After the holding program was completed, the sample was taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0103] Break the quartz tube and remove the quenched TiZrCrMnFeCo. 0.2 Ni 0.8 The sample was transferred to a glove box, and the quenched sample was mechanically crushed using a stainless steel mortar. The crushed powder was then passed through a 300-mesh sieve to obtain TiZrCrMnFeCo, which can be used for hydrogen storage performance testing. 0.2 Ni 0.8 High-entropy alloy powder sample.
[0104] Comparative example: TiZrCrFeCoNi
[0105] The preparation method is as follows:
[0106] Titanium particles, zirconium blocks, chromium sheets, iron blocks, cobalt sheets, and nickel sheets with a purity ≥99.9% were selected. These metals were weighed out according to the elemental mass ratio of the chemical formula TiZrCrFeCoNi: 13.13 g of titanium, 25.02 g of zirconium, 14.26 g of chromium, 15.32 g of iron, 16.16 g of cobalt, and 16.10 g of nickel. The weighed metal raw materials were placed in a crucible of a vacuum arc furnace in order of increasing melting point. The furnace was evacuated to a vacuum level below 0.003 Pa, and then argon gas at 0.06 MPa was introduced as a protective gas. Arc vacuum melting was performed. After the alloy was completely melted and cooled, an alloy ingot was formed. The ingot was turned over and melted repeatedly four times to obtain the TiZrCrFeCoNi alloy ingot.
[0107] The TiZrCrFeCoNi ingot sample was wrapped in tantalum foil and placed in a quartz tube that can withstand a high temperature of 1200℃. The vacuum degree inside the quartz tube was reduced to below -0.09MPa using a vacuum mechanical pump. Then, the open end of the quartz tube was closed by burning it under an oxyhydrogen flame, thus achieving the purpose of sealing the quartz tube.
[0108] The high-temperature resistant quartz tube containing the TiZrCrFeCoNi ingot sample was placed in the isothermal zone of a vacuum tube furnace, and the heat treatment program was set as follows: the furnace temperature was raised from room temperature to 1000℃ in 180 minutes, and then held at 1000℃ for 18 hours. After the holding program was completed, the sample was taken out of the furnace and placed in a stainless steel bucket containing liquid nitrogen or cold water for quenching treatment.
[0109] The quartz tube was broken, and the quenched TiZrCrFeCoNi sample was taken out and transferred to a glove box. The quenched sample was mechanically crushed using a stainless steel mortar. The crushed powder was passed through a 300-mesh sieve to obtain a TiZrCrFeCoNi high-entropy alloy powder sample that can be used for hydrogen storage performance testing.
[0110] Performance testing:
[0111] One gram of TiZrCrMnFeCo high-entropy alloy powder from Example 1 was placed in a stainless steel cylindrical container and then placed in a reactor. After evacuation, the temperature was raised to 400°C, and evacuation continued for 30 minutes. Then, the vacuum valve was closed, and high-purity hydrogen gas at 5 MPa was introduced. The environment of 400°C and 5 MPa hydrogen pressure was maintained for 2 hours to fully activate the sample. The sample chamber and testing system were then evacuated to a vacuum state using a mechanical pump, and the temperature was lowered to room temperature. The alloy powder was subjected to multiple hydrogen absorption and desorption cycles using a fully automated Sieverts testing instrument to conduct hydrogenation and dehydrogenation performance tests.
[0112] Take TiZrCrMnFeCo from Example 2 0.05 Ni 0.95One gram of high-entropy alloy powder was placed in a stainless steel cylindrical container within a reactor. After evacuation, the temperature was raised to 400°C, and evacuation continued for 60 minutes. The vacuum valve was then closed, and high-purity hydrogen gas at 5 MPa was introduced. This environment of 400°C and 5 MPa hydrogen pressure was maintained for 2 hours to fully activate the sample. A mechanical pump was then used to evacuate the sample chamber and testing system to a vacuum state, and the temperature was lowered to room temperature. Multiple hydrogen absorption and desorption cycles were performed on the alloy powder using a fully automated Sieverts testing instrument to test its hydrogenation and dehydrogenation performance.
[0113] Figure 1 shows the simulation results of the present invention TiZrCrMnFeCo obtained using Thermal-calc software. 1-x Ni x Variable-temperature uniaxial phase diagram of alloys (0≤x<1);
[0114] Figure 2 The XRD spectra of the hydrogen storage high-entropy alloys in Examples 1 and 2 are shown. The phase composition and microstructure of the alloys were analyzed by XRD, and it was found that the alloys have a C14 Laves single-phase structure.
[0115] Figure 3-6 The figures show the hydrogen absorption and desorption kinetics curves of the high-entropy hydrogen storage alloys in Examples 1-4 at room temperature. The hydrogen absorption / desorption kinetics curves of the alloys were tested using a fully automated Sieverts system, and it was found that the alloys could reach hydrogen absorption / desorption saturation within 150 s, proving that the system has the ability to rapidly absorb / desorb hydrogen at room temperature.
[0116] Figure 7-10 The figures show the PCT curves of the hydrogen storage high-entropy alloys in Examples 1-4 at room temperature. The tests were performed using a fully automated Sieverts system. A small hysteresis was found between the hydrogen release curve and the hydrogen absorption curve, indicating that almost all the absorbed hydrogen can be released, proving that the alloy has excellent hydrogen absorption and desorption performance at room temperature.
[0117] The gaseous cycling hydrogen storage performance of the alloy was tested, and the results are shown in Table 1.
[0118] Table 1. Hydrogen storage capacity and cycle stability of hydrogen storage alloys in Examples 1-4 and Comparative Example 1 of the present invention.
[0119]
[0120]
[0121] C max —Initial hydrogen absorption (wt.%) at an initial hydrogen pressure of 5 MPa and a temperature of 25°C;
[0122] C1—Hydrogen absorption capacity (wt.%) of the alloy after activation at 5 MPa and 25 °C;
[0123] C50 — Hydrogen absorption (wt.%) of the alloy after the 50th hydrogen absorption / desorption cycle at 5 MPa and 25 °C;
[0124] S 50 =C 50 / C1×100%, where C1 is the hydrogen absorption capacity of the activated alloy, C 50 Hydrogen absorption after the 50th cycle.
[0125] The results in Table 1 show that the hydrogen storage performance of the alloy of the present invention is significantly improved at low temperatures, and the alloy has good hydrogen absorption and desorption cycle stability.
[0126] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An AB2-type Laves phase hydrogen storage high-entropy alloy, characterized in that, The chemical formula of the hydrogen storage high-entropy alloy is: TiZrCrMnFeCo 1-x Ni x In the chemical formula, x represents the atomic ratio, where 0 ≤ x < 1; The hydrogen storage high-entropy alloy has a single C14 Laves phase structure, and the C14 Laves phase is a hexagonal structure. In the hydrogen storage high-entropy alloy, Ti, Zr, Cr, Mn, Fe, Co and optional Ni atoms are randomly distributed on the lattice sites of the C14 Laves phase structure, exhibiting a long-range disordered structure. The hydrogen storage high-entropy alloy has a high-abundance C14 Laves phase structure, a space group of P63 / mmc, a lattice constant of a = 0.49 ± 0.01 nm, c = 0.81 ± 0.01 nm, and a grain size of 100-300 μm. The hydrogen storage high-entropy alloy is prepared by melting, encapsulation, heat treatment, and rapid quenching.
2. The AB2-type Laves phase hydrogen storage high-entropy alloy according to claim 1, characterized in that, In the chemical formula, 0.5 ≤ x ≤ 0.
95.
3. A method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy according to any one of claims 1-2, characterized in that, The preparation method involves arc vacuum melting of metal raw materials under an inert atmosphere, followed by heat treatment and rapid cooling after packaging.
4. The method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy according to claim 3, characterized in that, The preparation method includes: S1, according to the chemical formula TiZrCrMnFeCo 1-x Ni x The raw materials are prepared with a purity of ≥99.9%. Under an inert atmosphere, the metal raw materials are placed in the crucible of an electric arc furnace and subjected to electric arc vacuum melting. After the alloy is completely melted and cooled, an alloy ingot is formed. The alloy ingot is turned over and melted repeatedly 3-5 times to obtain an ingot sample of the hydrogen storage high entropy alloy. S2, after wrapping the ingot sample with tantalum foil, seal it in a high-temperature resistant quartz tube filled with inert gas; S3, the ingot sample encapsulated in the quartz tube is subjected to quenching treatment, which includes heat treatment and rapid cooling. S4. The quenched alloy sample is mechanically crushed to obtain the finished AB2 type Laves phase hydrogen storage high-entropy alloy.
5. The method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy according to claim 4, characterized in that, In step S1, the metal raw materials are placed in the electric arc furnace crucible from bottom to top in order of increasing melting point.
6. The method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy according to claim 4, characterized in that, In S1, the vacuum degree of the electric arc vacuum melting is (0.3-0.5)×10⁻⁶. -2 Pa.
7. The method for preparing the AB2 type Laves phase hydrogen storage high-entropy alloy according to claim 4, characterized in that, In step S3, the heat treatment heating rate is 5-10 ℃ / min, the holding temperature is 900-1200 ℃, and the holding time is 12-24h.
8. The application of an AB2-type Laves-phase hydrogen storage high-entropy alloy according to any one of claims 1-2 or an AB2-type Laves-phase hydrogen storage high-entropy alloy obtained by the preparation method according to any one of claims 3-7 in hydrogen storage, characterized in that, AB2 type Laves phase hydrogen storage high-entropy alloy absorbs hydrogen at 350-400 ℃ and 3-5 MPa for 2-3 cycles to obtain the activity of hydrogen storage high-entropy alloy, and then it is used for hydrogen storage.
Citation Information
Patent Citations
Hydrogen compression material of metal hydride
CN1789455A